2009
DOI: 10.1002/hep.23222
|View full text |Cite
|
Sign up to set email alerts
|

Role of β3-adrenoceptors for intrahepatic resistance and portal hypertension in liver cirrhosis

Abstract: I ncreased intrahepatic resistance to portal flow 1 and decreased splanchnic vascular resistance 2 cause portal hypertension in liver cirrhosis. Dysregulation of intracellular vasoconstrictive Rho-kinase-mediated pathways may contribute to both processes. According to our findings, it is overactivated in the liver and dysfunctional in splanchnic vessels. [2][3][4][5][6][7] Reduction of extrahepatic vascular resistance leads to hyperdynamic circulation characterized by increased cardiac output and decreased sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 51 publications
(99 reference statements)
2
82
0
2
Order By: Relevance
“…The slight difference may be attributed either to experimental techniques and/or species differences. Recently, Trebicka et al (2009) detected the presence of ADRB3 in the liver of humans and rats, and found that ADRB3 was involved in portal hypertension in liver cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…The slight difference may be attributed either to experimental techniques and/or species differences. Recently, Trebicka et al (2009) detected the presence of ADRB3 in the liver of humans and rats, and found that ADRB3 was involved in portal hypertension in liver cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Additional agents with impact on HSC activation and contractility include mitochondrial antioxidants [95,96], renin-angiotensin system inhibitors [97], and relaxin [98]. Finally, selective Experimental Intestinal decontamination by rifaximin blocks TLR4-mediated activation of HSCs and modulates FXR signaling by changing intestinal bile acid composition associated with reduced fibrosis, angiogenesis, and PVP in experimental PHT [69] beta3 receptor agonists induce relaxation of HSCs via cAMP accumulation and Rho-kinase inhibition with no effect on normal PVP, indicating that these drugs primarily target the dynamic components of IHVR [99,100]. FXR has recently become a major pharmacological target in NAFLD owing to its complex role in bile acid and lipid metabolism, inflammation, and fibrosis [101].…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…Hemodynamic studies were performed under ketamine/xylazine anesthesia (78mg/kg / 12.5mg/kg i.p.) as previously described [14][15][16][17]. Rats were fasted overnight but allowed free access to water.…”
Section: Animalsmentioning
confidence: 99%
“…Hemodynamics were investigated using the coloured microsphere technique as previously described [14][15][16][17]. The colored microsphere technique was validated by the more frequently used radioactive microsphere method [18].…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation